ROLE OF LEADERSHIP AND EMPLOYEE MOTIVATION IN IMPROVING BUREAUCRATIC INTEGRITY PERFORMANCE AT KPKNL PEKALONGAN - Dalfin Ponco Nugroho (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
The Ministry of Administrative and Bureaucratic compile a grand design to improve bureaucratic services as a whole. The reason for the initiation of this program in the vertical unit of Ministries/Agencies is because in general the governance system in Indonesia is still not fully oriented towards the implementation of the principles of good governance (good government governance) and there are still gaps in corruption and fraud. The purpose of this study was to explore leadership patterns, investigate employee motivation, trace the problems faced, and describe the organizational strategy of the Pekalongan KPKNL organization to achieve integrity performance based on facts and data derived from interviews, observations, behavior patterns, body language, and the beliefs of the informants. The resource persons in this study were consisting of one Head of the Pekalongan KPKNL Office as the subject informant and 7 (seven) Section Heads as triangulation informants. Data collection methods used are field research. Data analysis was performed using qualitative data analysis methods with a phenomenological crisis approach with data processing methods through the NVIVO application. The analysis results show that the leader is expected to become a role model by providing direction, guiding the communication room and monitoring and evaluating the implementation of activities. Keywords: Leadership, Employee Motivation, Performance of Bureaucratic Integrity